(untitled) (The Peerian Journal, 2023)
The article discusses the role and place of health insurance in protecting the rights and legitimate interests of citizens. The author also touched upon the civil legal status of the insurance contract. The legal and theoretical aspects of the formation and development of a health insurance contract are also substantiated by reference to the scientific developments cited by the author and carried out to date in the field. In addition, the author puts forward substantiated proposals to improve the legislation governing the contract of health insurance.